Egzystencjalne doznania matek samotnie wychowujących dzieci z niepełnosprawnością intelektualną w stopniu głębokim i ich wybrane psycho-socjo-pedagogiczne uwarunkowania - Aksamit, Diana (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The autopsy of mothers raising adult children with profound intellectual disability is a documentation of maternity that varies from the commonly accepted role model of the mother and the role of the woman. Narrative conversations show that this group of women is struggling with many difficult experiences and emotions related to their own existence. The purpose of this article is the analysis of the existential experiences of the examined mothers in the level of reflection and the questions “why me?”, the meaning of life and the future. An attempt will also be made to find determinants conditioning them.